Retrospective study revealed integration of CNV-seq and karyotype analysis is an effective strategy for prenatal diagnosis of chromosomal abnormalities - Ge, Yunsheng; Chen, Jiayan; Huang, Yanru; Shao, Di; Wang, Wenbo; Cai, Meijiao; Tan, Meihua; Zhang, Jian (Frontiers in Genetics, 2024)
Fetal chromosomal abnormalities are the main cause of adverse pregnancy outcomes and are the focus of invasive prenatal diagnosis. Recent studies have demonstrated that various techniques have distinct advantages. Achieving high-resolution and effective prenatal chromosomal abnormality diagnosis requires a multi-technology integration strategy. Based on retrospective samples from a single center, we propose that integrating CNV-seq and karyotype analysis is an effective strategy for prenatal diagnosis of chromosomal abnormalities. In this study, 13.80% of the pregnant women (347/2514) were found to have likely pathogenic or pathogenic fetal chromosomal abnormalities using this integrated approach. Among these cases, 53.89% (187/347) had consistent chromosomal abnormalities detected by both CNV-seq and karyotyping analysis, while 19.02% (66/347) and 27.09% (94/347) of cases were diagnosed solely by CNV-seq or karyotyping, respectively. Fetal chromosomal abnormalities were identified in 18.39% of samples with abnormal ultrasound, which was significantly higher than the percentage found in samples with normal ultrasound (P < 0.001). Samples with multiple ultrasound abnormalities and single-indicator ultrasound abnormalities such as nasal bone dysplasia, renal dysplasia, or echogenic fetal bowel also had higher rates of chromosomal abnormalities (P < 0.05) compared to normal samples. Analyzing samples with Trio family data (N=521) revealed that about 94% of variants of uncertain significance were inherited from parents and were non-pathogenic. Overall, integrating CNV-seq and karyotype analysis is an effective strategy for prenatal diagnosis of chromosomal abnormalities. This study provides valuable insights for correlating prenatal screening indicators with chromosomal abnormalities.